Keunggulan Psychological Empowerment bagi Karyawan PT Pelabuhan Indonesia (Persero) Sub Regional Jawa - Ni'mah, Tsinta Alfiyatin; Frianto, Agus (Universitas Negeri Surabaya, 2025)
This study aims to examine the effect of job crafting on work engagement, with psychological empowerment as a mediating variable among employees of PT XYZ. The research uses a quantitative approach with a saturated sampling technique, involving the entire population of 100 employees as respondents. Data were analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with the help of SmartPLS 3.0 software. The findings reveal that job crafting does not have a significant direct effect on work engagement. However, job crafting has a positive and significant effect on psychological empowerment. Additionally, psychological empowerment positively and significantly influences work engagement. Importantly, the study finds that psychological empowerment serves as a significant mediating variable in the relationship between job crafting and work engagement. These results indicate that while job crafting alone may not directly enhance employee engagement, it can foster psychological empowerment, which in turn strengthens engagement. The study highlights the importance of psychological empowerment in the workplace, suggesting that organisations should focus on strategies that enhance employees’ sense of autonomy, competence, and impact to improve engagement levels. Overall, the research contributes to the understanding of employee motivation and engagement by emphasising the mediating role of psychological empowerment in organizational behaviour.